RELASI KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi Kasus di Poltekkes Surabaya) - Anshori, M. Isa (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2011)
Organizational Citizenship Behavior (OCB) is improving organizational efficiency and effectiveness by contributing toward resource transformation, innovation and adaptation ability (Williams and Anderson, 1991). The number of employees in Poltekkes Surabaya who are divided into various divisions becomes a problem for human resources management. Therefore, Poltekkes Surabaya directorâs managerial ability is greatly determined to organize human resources in order to create an effective and productive organization. In order to find out the relationship between job satisfaction and organizational commitment with organizational citizenship behavior in Health Polytechnic of Surabaya. The research used cross sectional design with subject of Health Polytechnic of Surabaya employees. In order to examine Organizational Citizenship Behavior, the research instrument being used was The Origin Organizational Citizenship Behaviors Questionnaire by Morrison (1994) which already used by Muchiri (2002). Job satisfaction was measured by using Minnesota satisfaction questioner. Organizationâs commitment is measured by using questioner which is presented by Allen and Meyer (1990); Panggabean (2004). The research showed that there was a relationship between job satisfaction with OCB with r=0,407; R2 = 0,165 and p Value = 0,000. There was a relationship between organizationâs commitment with significant OCB with r =0,2888; R2 = 0,83 and p Value = 0,001. Therefore, there was a significant relationship between job satisfaction and organizational commitment with organizational citizenship behavior with r=0,441; R2 = 0,194 and p Value = 0,000. In summary, there was a positive and significant relationship between job satisfaction with organizational citizenship behavior. There was a positive and significant relationship between organizationâs commitment with organizational citizenship behavior. There was a positive and significant relationship between job satisfaction and organizational commitment with organizational citizenship behavior